Feasibility of chemical screening of urine for neuroblastoma case finding in infancy in Quebec. - Scriver, C R (1987)
Neuroblastoma is the most common fatal solid tumour of childhood. Studies in Japan suggest that screening urine at 6 months for tumour-derived metabolites greatly improves early case finding and prognosis. The incidence rate of neuroblastoma in Quebec is at least 1 per 10,330 live births, higher than that of all other diseases responding to early treatment except congenital hypothyroidism screened for in the Quebec Network of Genetic Medicine. The feasibility of chemical screening of urine for elevated levels of homovanillic acid and vanillylmandelic acid in Quebec was assessed. The cost-effectiveness of screening 100,000 infants per year would be high (cost-benefit ratio 2.4), with a net saving of about $280,000 and eight lives per year. The estimated cost of adding neuroblastoma screening to the existing urine metabolite screening program is $70,700. The apparent sensitivity of the proposed test is 0.859 and the rate of false-positive results about 0.1%, both acceptable values. The attitude of potential participants toward the present urine screening program and the addition of a "tumour test" was positive. The results indicate that a pilot study of neuroblastoma screening in Quebec could be undertaken.